Clinical evaluation of skin lesions among patients with systemic lupus erythematosus: Experience from a tertiary care centre (Bangabandhu Sheikh Mujib Medical University Journal, 2024)
Background: Lupus patients frequently exhibit specific and nonspecific skin lesions and lesions associated with skin infections. This study aimed to determine the frequency of lupus-specific and non-specific skin lesions and the incidence of skin infections.Methods: This study was conducted in the Department of Rheumatology at Bangabandhu Sheikh Mujib Medical University (BSMMU), Dhaka, Bangladesh, from 2014 to 2016. After obtaining ethical clearance from the Institutional Review Board of BSMMU, 136 consecutive patients fulfilling the ACR criteria for SLE were enrolled and followed up for at least one year. A dermatologist confirmed lupus-specific, non-specific, and skin lesions related to infections and noted them in a datasheet. Relevant investigations were performed at baseline and during subsequent follow-up visits. Results: One hundred thirty-one patients completed their follow-up period. The mean (standard deviation) follow-up period was 13.3 (2.0) months. The patients' mean (standard deviation) age was 28.8 (8.2) years. Skin lesions and skin infections were present in 71.8% and 26.7%, respectively of patients. Common lupus-specific lesions were malar rash (75.4%) and DLE (12.3%). Photosensitivity (72.6%), non-scarring alopecia (67.9%), mucosal ulcers (47.6%), Raynaud’s phenomenon (23.8%), and hyperpigmentation (23.8%) were the prevalent lupus non-specific skin lesions. The common skin infections were tinea (42.9%), herpes infection (34.3%), paronychia (20%), and scabies (17%).Conclusions: Skin lesions related to infections were common, along with lupus-specific and nonspecific lesions skin lesions. Tinea and herpes infections were more common skin infections.